Fatty acid Composition and Antimicrobial Activity of Celtis australis L. Fruits - Badoni, R.; Semwal, D. K.; Rawat, U. (Journal of Scientific Research, 2010)
Methyl esters of fatty acid obtained from Celtis australis fruits were subjected to GC-MS in order to determine the identity and concentration of its constituents. Methyl oleate (25.7%), methyl palmitate (22.2%), methyl tricosanoate (13.3%), methyl lineolate (7.8%), methyl dotriacentanoate (2.6%) and methyl 14-acetylhydroxypalmitate (2.1%) were the major constituents out of total characterized composition (95.455%) of fatty acid. The ethanolic extract of fruits was used for evaluating its antimicrobial activity against Staphylococcus aureus, Pseudomonas auroginosa, Escherichia coli and Bacillus subtilis. The extract showed significant results against P. auroginosa and E. coli. The antimicrobial activity and fatty acid analysis of C. australis of fatty acid fruits has been carried out for the first time. Keywords: Celtis australis; Ulmaceae; methyl oleate; methyl tricosanoate; Pseudomonas auroginosa; Escherichia coli. © 2010 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v2i2.4056 J. Sci. Res. 2 (2), 397-402 (2010)